Stock market comovements in Central Europe: Evidence from the asymmetric DCC model - Gjika, Dritan; Horváth, Roman (Economic modelling)
We examine time-varying stock market comovements in Central Europe employing the asymmetric dynamic conditional correlation multivariate GARCH model. Using daily data from 2001 to 2011, we find that the correlations among stock markets in Central Europe and between Central Europe vis-à-vis the euro area are strong. The correlations increased over time, particularly after their EU entry and largely remained at these levels during the financial crisis. The stock markets exhibit asymmetry in the conditional variances and to a certain extent in the conditional correlations as well, pointing to the importance of applying a sufficiently flexible econometric framework. The conditional variances and correlations are positively related, suggesting that the diversification benefits decrease disproportionally during volatile periods. •Central European stock markets are strongly correlated with Western Europe.•Financial crisis increased the correlations.•Conditional volatility and correlations are positively related.•Conditional volatility and correlation are often asymmetric.